SEMANTIC ANALYSIS OF VERB WAZAN IN THE POETRY OF JALALUDDIN RUMI - Yazid Zidan Lubis, Muhammad Farhan (Jurnal Al-Hibru, 2025)
This study aims to analyze the forms of the wazan fi’il in the Arabic poem entitled “دعاء” by Jalaluddin Rumi using a semantic approach. Jalaluddin Rumi is known as a great Sufi figure whose poems are rich in spiritual meaning, symbolism, and inner expressions. One of the linguistic elements that strengthens this meaning is the use of the form of fi’il (verb) which has a certain pattern or wazan in Arabic. This study uses a qualitative method of library research, by analyzing each verse of the poem morphosemantically, namely by looking at the relationship between the verb pattern and the meaning produced. The primary data comes from the text of the poem, while secondary data is obtained from Arabic linguistic references, sharaf science, and Sufism literature. The results of the analysis show that Rumi's choice of wazan form is very strategic and full of meaning, such as the use of wazan أفعل، تفعّل، فاعل، انفعل which indicates the meaning of movement, will, transformation of the soul, and surrender. Each fi'il in this poem does not stand alone, but forms a deep spiritual narrative. This study confirms that the analysis of wazan fi'il can be an important tool in understanding the inner message and linguistic aesthetics of Sufi poetry. This broadens the scope of Arabic literary studies from only thematic studies to a deeper structural-semantic analysis.